SUBSTRATE TEMPERATURE EFFECT ON ELECTRICAL PROPERTIES THIN LAYER SEMICONDUCTOR PbS, PbSe AND PbTe PREPARED BY VACUUM EVAPORATION TECHNIQUE - abdul mafahir iim; sutjitno tjipto; Ariswan Ariswan (Prodi Fisika, Departemen Pendidikan Fisika, 2016)
This research aims to produce a thin layer of semiconductor with PbS, PbSe and PbTe material by vacuum evaporation techniques and to find out electrical properties of these materials. Thin layer was produced by using vacuum evaporation techniques. Varied temperature of substrate is used as parameters during preparation,ie without heating (sample 1), 200 ℃ (sample 2), 350 ℃ (sample 3), and 500 ℃ (sample 4). Electrical properties are characterized by using a four point probe (FPP). Results showed that this thin layer of PbS, PbSe and PbTe is type N semiconductor with resistivity in Ω.cm to Ω.cm oreder Keywords: thin layer, evaporation, electrical properties